ANALYSIS OF MARKET MARGINS AND MARKETING EFFICIENCY IN THE SOYBEAN SUPPLY CHAIN: EVIDENCE FROM BARUTEEN LGA, KWARA STATE - Hussaina Ummikhanni Mahmud; Nofiu Babatunde Nofiu; Aisha Mohammed Lafia (Malete Journal of Accounting and Finance, 2024)
Soyabean is produced mainly in small holder farms in Baruteen LGA of Kwara State, but the soybean marketers in Baruteen are faced with a lot of challenges ranging from high transaction costs, fluctuations in soybeans prices, limited storage capacity, access to credit, down to inadequate distribution networks. This making profit maximization difficult. This study examines the market margin and efficiency of wholesaler soybean supply chain in Baruteen, Nigeria. Data for study were obtained from primary sources with the aid of a well-structured questionnaire. The study used cost-benefit analysis to estimate market margin and marketing efficiency of soybeans. Our results show that an average of 17.5bags were sold by marketers at every market day with average profit margin per marketer of ₦5,188, and a market margin of 33.14%. However, the marketing efficiency of soybean in the area is relatively low, at 15.37%. These findings suggest that while the sales of soybeans are profitable in Baruteen, there are inefficiencies in the marketing channel that need to be addressed in order to improve the performance of the soybean marketers. The study recommends strategies to improve marketing efficiency, such as reducing transaction costs, improving market access, and enhancing the productivity of soybean marketers.